Cryogen-free comprehensive heartcut multidimensional gas chromatography using a Deans switch for improved analysis of petrochemical products derived from palmitic acid oxidation. Issue 43 (2nd November 2020) - Thongdorn-Ae, Nilobon; Nhujak, Thumnoon; Janta, Pannipa; Rueangthaweep, Atitarn; Hinchiranan, Napida; Kulsing, Chadin
Abstract : Comprehensive heartcut multidimensional gas chromatography was applied with example application for analysis of a sample obtained from palmitic acid oxidation in a Rancimat instrument. Abstract : Comprehensive heartcut multidimensional gas chromatography was applied with example application for analysis of a sample obtained from palmitic acid oxidation in a Rancimat instrument. The system utilized a single Deans switch (DS) located between first dimensional semi-standard nonpolar (30 m) and second dimensional polar (60 m) columns. A cyclic multiple heartcut strategy consisting of 150 heartcuts with a 0.2 min window was applied offering comprehensive analysis and injection of a narrow band of compounds onto the second column without use of cryogenic trapping devices. Untargeted compound analysis of the sample prepared by solid phase micro-extraction was performed based on match between the experimental MS spectra and first dimensional retention indices with that from the NIST library. The sample contained the major compounds of 2-octanone, 1-methylcyclohexanol, 2, 3, 6-trimethylphenol, 3-phenylpropanol and 2-nonanone. This approach was then evaluated based on peak capacity and the number of identified compounds. Compared with one dimensional gas chromatography providing a total peak capacity of 172 and 43 identified compounds, the analysis performance was much more improved with a capacity of 5840 and 235 identified compounds by using comprehensive heartcut multidimensional gas chromatography with the total analysis time of 15.3 h. By comparison within the same set of identified compounds, the one dimensional and multidimensional approaches provided the MS match scores of 769 ± 81 and 836 ± 88, respectively. In addition, the nonlinear relationship between the analysis time and number of identifiable peaks was calculated according to the set of 235 compounds. This revealed that the analysis time could be shortened with the compensation of lower separation performance, where application of a 2.5 min heartcut window with the total analysis time of 1.2 h could result in the total peak capacity of 390 with 150 identifiable compounds.